Regulatory Updates: Maine Milk Commission - Staff, Editorial (Maine Policy Review, 1993)
Maine Policy Review has taken a particular interest in the activities of Maine’s key regulatory agencies, such as the Public Utilities Commission and the Board of Environmental Protection. The state also has a number of regulatory agencies with jurisdictions over relatively narrow interests or industries. Because of their narrow mission, these agencies often do not attract regular media attention. In this issue, MPR continues its policy of highlighting these "other" regulatory boards, in this case the Maine Milk Commission, providing readers with general and contextual information about these bodies.